Sleep quality: A common thread linking depression, post-traumatic stress, and post-concussive symptoms to biomarkers of neurodegeneration following traumatic brain injury. (16th April 2022) - Gottshall, Jackie L.; Agyemang, Amma A.; O'Neil, Maya; Wei, Guo; Presson, Angela; Hewins, Bryson; Fisher, Daniel; Mithani, Sara; Shahim, Pashtun; Pugh, Mary Jo; Wilde, Elisabeth A.; Devoto, Christina; et al.
ABSTRACT: Objective: Following mild traumatic brain injury (mTBI), many individuals suffer from persistent post-concussive, depressive, post-traumatic stress, and sleep-related symptoms. Findings from self-report scales link these symptoms to biomarkers of neurodegeneration, although the underlying pathophysiology is unclear. Each linked self-report scale includes sleep items, raising the possibility that despite varied symptomology, disordered sleep may underlie these associations. To isolate sleep effects, we examined associations between post-mTBI biomarkers of neurodegeneration and symptom scales according to composite, non-sleep, and sleep components. Methods: Plasma biomarkers and self-report scales were obtained from 143 mTBI-positive warfighters. Pearson's correlations and regression models were constructed to estimate associations between total, sleep, and non-sleep scale items with biomarker levels, and with measured sleep quality. Results: Symptom severity positively correlated with biomarker levels across scales. Biomarker associations were largely unchanged when sleep items were included, excluded, or considered in isolation. Pittsburgh Sleep Quality Index demonstrated strong correlations with sleep and non-sleep items of all scales. Conclusion: The congruency of associations raises the possibility of a common pathophysiological process underlying differing symptomologies. Given its role in neurodegeneration and mood dysregulation, sleep physiology seems a likely candidate. Future longitudinal studies should test this hypothesis, with a focus on identifying novel sleep-related therapeutic targets.